REVIEW: BAHAN AQUAFEED YANG BERPOTENSI MENINGKATKAN LAJU PERTUMBUHAN DAN KUALITAS PADA Oreochromis niloticus - Yuliana Helen Setia Putra; Kusdianti Kusdianti (Gunung Djati Conference Series, 2023)
Oreochromis niloticus is the second most widely cultivated aquaculture product worldwide. Fish-meal (FM) and fish oil (FO) as the main ingredients in the manufacture of aquaculture feed can cause ongoing problems. An alternative feed source is needed with a good aquafeed formula for Tilapia with good ingredients, preferably FMFO and adding one that can increase the growth rate of fish. The method used in this review is a literature study. Making diet formulations on each alternative ingredient, experimental design and sampling, analytical calculations and nutritional content of fish samples. The results of alternative feeds that increase the growth rate of Tilapia on microalgae with the most effective formulation, 100% microalgae (100NS), and yeast fermentation Poultry by-product meal with the most effective formulation as much as 20% FPBM. Alternative feed ingredients that can replace FMFO in these studies that can increase growth in Tilapia are feeds that are given alternative ingredients, microalgae and fermented yeast Poultry by-product meal. In the diet feed, both microalgae and yeast fermented feeds. Poultry by-products appear to produce better FCR and SGR than conventional feeds.